Limitations of ion mobility spectrometry‐mass spectrometry for the relative quantification of architectural isomeric polymers: A case study. (8th February 2020) - Liénard, Romain; Duez, Quentin; Grayson, Scott M.; Gerbaux, Pascal; Coulembier, Olivier; De Winter, Julien
Rationale: Since their discovery, cyclic polymers have attracted great interest because of their unique properties. Today, the preparation of these macrocyclic structures still remains a challenge for polymer chemists, and most of the preparation pathways lead to an inescapable contamination by linear by‐products. As the properties of the polymers are closely related to their structure, it is of prime importance to be able to assess the architectural purity of a sample. Methods: In this work, the suitability of ion mobility spectrometry‐mass spectrometry (IMS‐MS) for the quantification of two isomers was investigated. A cyclic poly(L‐lactide) was prepared through photodimerization of its linear homologue. Since IMS‐MS can be used to differentiate cyclic polymer ions from their linear analogues because of their more compact three‐dimensional conformation, the present work envisaged the use of IMS‐MS for the quantification of residual linear polymers within the cyclic polymer sample. Results: Using the standard addition method to plot calibration curves, the fraction of linear contaminants in the sample was determined. By doing so, unrealistically high values of contamination were measured. Conclusions: These results were explained by an ionization efficiency issue. This work underlines some intrinsic limitations when using IMS‐MS in the context of the relative quantification of isomers having different ionization efficiencies. Nevertheless, the linear‐to‐cyclic ratio can be roughly estimated by this method.